Factors Affecting Job Satisfaction of Hospital’s Health Personnels: A Scoping Review - Handayani, Titik; Jati, Sutopo Patria; Dharmawan, Yudhy (Journal of Public Health for Tropical and Coastal Region, 2025)
Introduction: Medical personnel make a crucial contribution to the standard of healthcare provided to patients. The extent of work contentment among medical staff members will affect the quality of health services. This research aimed to identify the factors that affect job satisfaction of hospital’s health personnels.Methods : This scoping review used sources from ScienceDirect and Scopus databases. The keywords used for manuscript searching were: ”factors” AND “job satisfaction” OR “job happiness” OR “career contentment” AND “medical staff” OR “medical professional” AND “hospital”. The Inclusion criteria were: published in 2020-2024 range, English language, freely accessible.Results: The total number of articles found which were matched with the criteria was 38 articles. The studies were conducted throughout the global during and after pandemics. The intrinsic factors of job satisfaction mentioned were about burn out, workload, psychosocial problems, and sense of achievement, while the extrinsic factor included working environment and condition, leadership style, income, teamwork and empowerment through training and education.Conclusion: Factors affecting job satisfaction in medical personnel included intrinsic factors of workload, psychosocial problems, discomfort, demands and sense of achievement and extrinsic factors of work environment, working conditions, leadership style, salary, teamwork, interpersonal relationships and employee empowerment.